The Operation of Natural Selection through Differential Mortality: The Detva Population during the Great Epidemics, 1831–1920 - Ján Golian; Grażyna Liczbińska (Przeszłość Demograficzna Polski, 2023)
This paper centers on the infectious disease epidemics which swept through the Detva region, located in Upper Hungary (currently the territory of central Slovakia) in 1831–1920. The goal of this study is twofold: firstly, to examine the extent to which deaths caused by epidemics of infectious disease influenced life expectancy, the proportion of the deceased and survivors, and the probability of death in the Detva population, and secondly, to measure selection pressures through differential mortality, with a focus on deaths caused by infectious disease epidemics. We used individual information on age at death and causes of death in the Detva region, derived from the Detva parish records (N = 29,338). Infectious disease epidemics were the main regulator of mortality in the Detva region, as confirmed by our findings. Excluding deaths caused by infectious diseases from the dataset raised the life expectancy of a new-born and of an adult by 1–5 years and 1–2 years, respectively. The fraction of those surviving to the age of 5, the onset of maturity (15 years) and the onset of senility (60 years) also increased, while there was a decline in the proportion of deceased and the probability of dying. When deaths caused by infectious disease epidemics were removed from the analyses, selection pressures also weakened, as evidenced by the values of measures for the operation of natural selection.